Substance-use disorders, personality traits, and sex differences in institutionalized adolescents. (2nd November 2018) - Habersaat, Stéphanie; Ramain, Julie; Mantzouranis, Gregory; Palix, Julie; Boonmann, Cyril; Fegert, Jörg M.; Schmeck, Klaus; Perler, Christian; Schmid, Marc; Urben, Sébastien
ABSTRACT: Background : Substance-use disorder (SUD) was found to be an aggravating factor to delinquency and is closely related to personality disorders (PDs). Objectives : The aim of this study was to investigate sex differences in the relationship between PD traits and SUD in adolescents institutionalized in child welfare and juvenile justice institutions. Methods : PD traits were measured dimensionally in a sample of 282 boys (69 with an SUD diagnosis) and 143 girls (45 with an SUD diagnosis) from child welfare and juvenile-justice institutions. Results : Logistic regressions showed that antisocial, borderline, and paranoid personality traits were positively associated with SUD, while obsessive compulsive personality traits were negatively related with SUD. Additionally, in institutionalized girls, self-defeating personality traits were associated with less risk of SUD. Conclusion : This study provides a relative evidence for sex specificities in the relation between PD traits and SUD.